Intra and postoperative complications in dental implant surgery. - de Paula, Mario André; Alvez Silva, Cleyton (Brazilian Journal of Implantology and Health Sciences, 2020)
In view of the development and success of dental implantology, surgeons expanded their indications. The constant arrival of new techniques and materials brought about by technological and scientific progress increases the scope of dental implantation possibilities. This evolution expanded the notion of risks in implant surgery to the possibility of injuries to anatomical structures with the complications that result from them. Thus, for the surgeon, knowledge of the various anatomical structures and obstacles, as well as their individual variations, are essential for performing all implant and pre-implant surgery. The successful outcome of any surgical procedure requires attention to a number of parameters related to the patient and dependent on the procedure. Good knowledge of surgical anatomy, experience and training in the fundamentals of internal medicine are important prerequisites for implant surgery to be predictable. In addition, adequate pre-surgical planning (anamnesis, objective examination, complementary diagnostic tests), the quality and quantity of bone available, a well-executed surgical technique, a good healing period and detailed postoperative instructions are factors that play a vital role in the success of dental implant surgery and osteointegration. The present work has as main objectives to know which are the main complications that may occur during and after dental implant surgeries and to know which prevention means are available to anticipate and avoid these complications.